Diarios de bicicleta: Procesos educativos vivenciados en la Ruta de las Emociones - Gonçalves-Junior, Luiz; Corrêa, Denise Aparecida [UNESP]; Carmo, Clayton da Silva; Arévalo, Sergio Toro (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2016)
The objective of the research was to identify and analyze educational processes experienced by a group of cyclotourists participating in the Environmental Education and Leisure Project, during a cyclotrip. Based on records in field diaries and qualitative analysis, the following categories emerged: Specific Technical Knowledge; Cycle-Empathy; Negotiation; Environmental Phenomenology. Categories allow the recognizion of various educational processes related to technical expertise on bicycle use, as well as some geographical aspects, many of which were possible only from the knowledge of local communities. Data show that the openness exposed by the cyclotourist also triggered empathic attitudes among group members and the people who inhabited the places covered, experiencing nature in depth. We consider the use of bicycles as encouragement for educational activities aimed at promoting critical experience of leisure and environmental education.
Bicycle diaries: Educational processes in the Emotions Route
Keywords: Cyclotrip; Educative processes; Environmental education; Leisure